FACIES AND ARCHITECTURAL ANALYSIS OF FLUVIAL DEPOSITS OF SAWAHTAMBANG FORMATION, OMBILIN BASIN, WEST SUMATERA - Fernando, Edo (2017)
The fluvial strata of Sawahtambang Formation have been the subject of systematic sedimentological studies. Detailed analyses of the facies, paleocurrents and sedimentary architecture were performed on the exposures. The cumulative stratigraphical thickness of the studied successions reaches abaout 145 m. Seven sedimentary facies were distinguished: fine grained massive (Fm), fine grained horizontal laminated sandstone (Sh), medium to coarse grained cross stratified sandstone (Sc), fine to coarse grained massive sandstone (Sm), fine to medium grained massive conglomerate (Gm), fine to medium grained cross stratified conglomerate (Gcm), and coarse grained cross stratified conglomerate (Gcc). Five architectural elements were identified: channel (CH), sand bed forms (SB), gravel bars and bed forms (GB), sediment gravity flow deposits (SG), and overbank fines (OF). All of these sediment represent braided river system, though the type or behaviour of these system differs at individual localities. Most of them were high energy, braided of low sinousity, laterally migrating braided streams of low sinousity, possibly forming braidplain fluvial environments were located on the Kayugadang Village. Deposit indicative of vertically aggrading streams of higher sinousity and lower energy fluvial environments were located on the Saringan and Kubang Sirakuk Village. Key words : sawahtambang formation, facies, architectural elements, braided river system